Placental insufficiency and threatened miscarriage: a modern view on the problem - S M Voevodin; T V Shemanaeva; A I Shegolev (IP Berlin A.V., 2017)
Analysis of clinical and morphological data of 101 cases complicated by placental insufficiency have performed. In all cases, pathomorphological verification of the placenta had carried out. Obstetric complications were accompanied by activation of immuno-inflammatory process in placental tissue.